Primerjava metod za geomorfometrične analize hrapavosti površja na primeru Vipavske doline ( = Comparison of methods for geomorphometric analysis of surface roughness in the Vipava valley) - Tomislav Popit (Geodetski Vestnik, 2016)
A method that gives the clearest individual geomorphometric elements for the requirements of spatial analysis was selected to define the spatial variability of landforms on primary bedrocks and their slope deposits on the northern edge of the Vipava Valley in Slovenia. We tested the most frequently used morphometric indicators of surface roughness, other than the curvature of the surface, and reviewed them based on their performance with lidar data. We analysed in detail five methods that can be used for surface roughness evaluation and that have a potential for the study of the bedrock and slope deposits. Height variability was identified as the most appropriate method. We have also found that maps of properly portrayed height variability can be an indispensable tool for geological and geomorphological mapping.